A Study on Correlation between Serum Cortisol and Stroke Severity with Serum Cortisol (Academia Journal of Medicine, 2020)
Background: The stress response that occurs after the event of acute stroke causes the activation of the hypothalamo–pituitary–adrenal (HPA)  axis. Certain studies have found that increased serum cortisol level in patients with acute stroke is related to larger infarct volume, greater  stroke severity and poor outcome, including death. Subjects and Methods: About 50 new cases of acute ischemic stroke patients, within 72  hours of the acute neurological event , who were admitted in the Sridevi Medical College & Hospital were included in the study. The study was  conducted for a period of 6 months.(June 2018-December 2018). CT Brain was taken during admission to confirm acute ischemic stroke.  NIHSS (National Institute of Health Stroke Scale)score for all the patients were assessed for severity at the time of admission. Results: Of the  50 cases, serum cortisol level of 23 cases were within normal limits(
Keywords: Acute ischemic stroke; HPA axis; serum cortisol; clinical severity; Functional outcome; stroke scales